Soya-beans as green manure in a maize intercropping system - Pandey, R.K.; Pendleton, J.W. (Cambridge University Press, 1986)
Two experiments were conducted over a two year period at the International Rice Research Institute (IRRI) in the Philippines to evaluate the effect of a soyabean green manure intercrop on the grain yield of maize. Three rows of soyabeans were interplanted at 50 cm spacing between maize rows 1.5 m apart. Forty two days after planting the two outside soyabean rows were ploughed into the maize rows in a traditional ‘hilling up’ operation. At the zero and lower nitrogen rates, the soyabean green manure resulted in significantly larger maize yields than when maize was grown without green manure, providing the equivalent of 28 kg N ha−1 on the zero nitrogen plots. A response to green manure was also seen at 25 and 50 kg N ha−1. Allowing the central soyabean row to grow to maturity provided additional yield and protein.